(Pushing) the Limits of Neuroplasticity Induced by Adult Language Acquisition - Maria Carmen Parafita Couto (Frontiers Research Topics, 2018)
Most adults attempt to learn a second or even third language at some point in their life. Since language exposure is one of the most intense cognitive training regimes one can encounter, it is not surprising that previous research has shown that multilingualism can induce profound change in the brain or 'neuroplasticity'.What remains unclear is the scope of such adult language learning induced neuroplasticity. In other words, much is yet to be investigated about the factors that limit or promote adult language learning induced neuroplasticity. On the one hand, the present research topic discusses research that sheds light on neural mechanisms that limit adult language learning induced neuroplasticity such as: neural mechanisms of first language interference in the acquisition of a second language and reduced opportunity for language induced neuroplasticity due to aging. On the other hand, the Research Topic discusses factors that could enhance non-native language learning (and underlying neuroplastic mechanisms), such as the duration of the training regime, language aptitude, and meta-linguistic awareness. Therefore, the goal of the present Research Topic is to examine both the limits of neuroplasticity in adult language learning and the ways to push beyond those limits. Understanding of such limits and frontiers to push beyond the limits is not only theoretically fundamental but could also have practical implications for enhancing language training programmes.